Synthesis and Characterization of Polyaniline Coated Carbon Black Composites - Mishra, Sarika; Nigam, A. C.; Gupta, G. S. (IJRDO-Journal of Applied Science, 2017)
Conducting polymer composites are examined universally for their use in various applications such as corrosion protection, electromagnetic interference shielding, and Solar cells and corrosion organic light emitting diode. In this coarse, here in, we made a strategy for homogeneous coating of polyaniline on carbon black for their potential use in different areas. Polyaniline coated carbon black shows larger surface area, high thermal stability, electrical conductivity and better corrosion resistance. Major application of Carbon black is as reinforcement in automobile tyres where it helps to conduct heat away from the treat and belt area of the tyre, reducing thermal damage and increasing its life. β– Naphthalenesulphonic acid (β–NSA) was used as surfactant and dopant which offers the homogeneous coating on carbon black. Polyaniline (PANI)–carbon black composites were prepared by chemical oxidative polymerization . The SEM of PANI– carbon black also revealed the nano porous nature of coating, which can be used for selective incorporation of other carbon forms. Morphology of PANI– carbon black displays the incorporation of carbon black in PANI matrix. Such prepared conformally polymer coated carbon black could be a auspicious candidate for next generation building block material in several applications.